THE IMPORTANCE OF USING ARTIFICIAL INTELLIGENCE TECHNOLOGIES IN IMPROVING THE QUALIFICATIONS AND DEVELOPING THE COMPETENCE OF GENERAL SCIENCE TEACHERS (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article presents an analysis of teachers' perceptions of artificial intelligence, its definitions, concepts, possibilities and importance of its application in the educational process. The importance of artificial intelligence technologies and types that educators can use in modern lessons is presented, and their use in teaching is recommended, which allows educators to increase teaching efficiency, save time and provide an individual approach to learners.